If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + 9 = Yt + -6 Reorder the terms: 9 + 7y = Yt + -6 Reorder the terms: 9 + 7y = -6 + tY Solving 9 + 7y = -6 + tY Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 7y = -6 + -9 + tY Combine like terms: 9 + -9 = 0 0 + 7y = -6 + -9 + tY 7y = -6 + -9 + tY Combine like terms: -6 + -9 = -15 7y = -15 + tY Divide each side by '7'. y = -2.142857143 + 0.1428571429tY Simplifying y = -2.142857143 + 0.1428571429tY
| h-18= | | -7(w-4)+3w-27=0 | | 16v^2+17v-45=0 | | 3w+4-w=5w+7-m | | 5m+4=4m | | -5(w-9)+8w+2= | | 2x^2-16x+29=0 | | -4x-7=-43 | | -6x-2=x-23 | | 5.3x+2=12.7-2 | | 7x/10=5 | | 3x-2/7=5/6 | | 6x-40=45 | | -6(4p+3)-49=5(2p+7) | | 4x^2=-24-20x | | 4.2x+31.5=-65.1 | | -86=4+10x | | 3.9x-13=1.7x+31 | | w^2+4w-124=0 | | 5/9(k-273.15) | | p=9+1.5(3) | | d/4-5 | | 3x+3x+4x=5 | | p=9+1.5(1) | | 3x+3x+4x/10=5 | | 7.2x-60=3.6x+30 | | x+4=-18 | | 6-14b=22 | | 2.3x+75.5=8.8x-22 | | 3-4x=-7-4s | | -2=(6+x)/10 | | 13x+14y=177 |